E-031 Mri selected elvo patients show favorable response to therapy at extended time from last seen well. (23rd July 2017) - Cristiano, B; Cicilioni, K; Pond, M; Lee, J; Promod, P; Oyoyo, U; Jacobson, J
Abstract : Background: Presently accepted criteria for ELVO intervention rely on time from last seen well (LSW) following conformation of LVO diagnosis and favorable baseline imaging. Many patients however present outside established treatment windows or with unknown LSW, and thus, represent a population of great relevance. Here we present in hospital and 90 day outcomes of a large patient cohort, many treated at extended LSW, after MRI assessment. Population: ELVO patients with isolated occlusion of the carotid terminus or M1 segment, baseline mRS ≤2, age ≥18, and no MRI contraindication. Methods: Regression analysis with primary outcome 90d mRS ≤2 and secondary outcomes in-hospital mortality, 90d mortality, 24 hour and discharge stroke severity (NIHSS). Results: From a stroke intervention dataset representing n=80 ELVO patients treated with thrombectomy between 12/25/2014 and 8/14/2016, n=40 cases were identified meeting inclusion criteria. Median patient age was 69, baseline NIHSS was 17.5, and mean CT ASPECTS was 8.78. 15/40 (37.5%) received IV tPA and the median presenting DWI core volume was 15 mL (IQR: 5.0–33.7). Median time to femoral access was 418 min (IQR: 281–936). TICI ≥2B recanalization success was 85%. No patient had PH2 intracranial hemorrhage, 1 had PH1, 3 HT1, and 2 SAH, none requiring additional intervention. 90d mRS ≤2 was 20%, in-hospital mortality was 12.5%, 90d mortality was 30%. All patients with 90d mRS ≤2 also had TICI ≥2B recanalization. Many patients (20/40) showed early response to therapy as defined by improvement in NIHSS≥4, an effect that was more likely with TICI ≥2B recanalization (OR 2.53 [95CI: 1.663–3.876]), and equally likely with femoral access before or after 6 hours LSW (OR 1.403 [95CI: 0.782–2.516]). The strongest predictor of 90d mRS ≤2 was baseline MRI core volume (b=−0.364, p=0.013). A similar and more robust effect was observed with discharge NIHSS (b=0.256, p < 0.001). Time to femoral access showed a weak interaction with 90 day outcome and discharge NIHSS although a few patients treated at very early time LSW (<3 hour) showed excellent early response to therapy. Conclusion: MRI selected ELVO patients represented in this cohort showed favorable response to therapy even at extended time from LSW. Although a few patients treated <3 hours LSW showed excellent response to therapy, MRI core volume was a better predictor of both in hospital and 90 day outcomes than time. Disclosures: B. Cristiano: None. K. Cicilioni: None. M. Pond: None. J. Lee: None. P. Promod: None. U. Oyoyo, : None. J. Jacobson: None.